An Analytical Study of Weakly Nonlinear Dynamics of a Walters' Liquid B around a Flexible Sheet Undergoing Super Linear Stretching. (24th October 2012) - Siddheshwar Siddheshwar, P. G. P. G.; Chan Chan, A. A.; Mahabaleswar Mahabaleswar, U. S. U. S.
Abstract : The paper discusses the boundary layer flow of Walters' liquid B over a stretching sheet. The stretching is assumed to be a quadratic function of the coordinate along the direction of stretching. The study encompasses within its realm both Walters' liquid B and second order liquid. The velocity distribution is obtained by solving the nonlinear governing differential equation. Analytical expressions are obtained for stream function and velocity components as functions of the viscoelastic and stretching related parameters. It is shown that the viscoelasticity goes hand in hand with quadratic stretching in enhancing the lifting of the liquid as we go along the sheet.